Factors Associated with the Nutritional Status of the Older Population - Abeer Brike Al-Mawlid , Halimah Ali Abeeri , Nawal Abdullah Dordeha , Fayzah Ali Alsomaly , Olfat Talal Bardisi , Laila Mohammed Baghsheer; Mona Abdullah Hakami , Waheed Qassem Eidah , Ayed Musleh Albuqami , Ghaida Ali Alhazmi , Bashayer Thamer Hussein Althaqafi (Migration Letters, 2022)
Background: The older population is increasing worldwide and in many countries older people will outstrip younger people in the near future. The percentage of elderly is growing rapidly and malnutrition is not uncommon in the elderly. Globally, older population (aged ≥60 years) comprise 11% of the total population, and 23% of them are malnourished. Lack of knowledge and education, adverse dietary habits, depression or psychological disorders, poor oral and dental health, disability, and diseases are the reported factors responsible for malnutrition among them. But there is scarce data on the factors associated with the nutritional status of the older population. The study aim: To identify the factors associated with their nutritional status of the older population. Methods: A cross-sectional study was conducted among 125 older individuals (male 59, female 66). The Mini Nutritional Assessment scale, Geriatric Depression Scale-Short Form, and Geriatric Oral Health Assessment Index were used for assessing the nutritional status, mental health status, and oral health quality of the respondents, respectively. Information on socio-demographic characteristics, comorbidities and dietary factors, and food behaviors were gathered by a pretested semi-structured questionnaire. Ethical approval was obtained from the Medical University. Results: The participants’ mean age was 67.9 ± 7.1 years. Most of them (53.6%) had no formal education. Among the respondents, 22.0% male and 28.8% female were malnourished. The proportion of malnourished and at risk of malnutrition among the respondents living without a partner was 28.6 and 65.3%, respectively. A significantly (p < 0.05) higher odds of having depression (OR 15.6; 95% CI 3.1–78.1), poor oral health (OR 7.3; 95% CI 1.3–41.8), and no formal education (OR 6.5; 95% CI 1.3–32.1) was observed among the malnourished respondents. Though it was not statistically significant, among the malnourished, 31.3, 25.0 and 25.0% avoided highly oily food, beef/mutton, and sugary food, respectively. Conclusions: More than two-thirds of the older population were malnourished or at risk of malnutrition, where the female respondents were more vulnerable. Depression, inadequate oral health, and lack of education were negatively associated with the nutritional status of the older population.